Kajian dan penulisan kearifan budaya Melayu Jambi dengan pendekatan jurnalisme sastra, berbasis penelitian budaya lokal - Eddy Pahar Harahap; Kamarudin Kamarudin (Universitas Lampung, 2021)
In the context of cultural wisdom, it is no longer seen as hereditary heritage but cultural wisdom is the strength of the creative industry based on cultural wisdom. Students of the language and literature study program who have writing and literary skills are able to study and write cultural wisdom. With the ability to study and write local wisdom allows students as; entrepreneurship, creator, humanist, writer based on the strategy of cultural wisdom values. The research focus is the study and writing of Jambi Malay cultural wisdom with a literary journalism approach. Literary journalism is a feature-oriented creative writing skill based on facts in the field. To achieve this, the study and discussion refers to the practice of improving learning; Research and development; Classroom Action Research, and Project-Based Learning. The results of research on student abilities; write the title of 'good' level, write the intro at 'good' level, the type of intro written; storytelling, descriptive, and questions, writing the atmosphere of the story as a result of observation at the 'medium' level, writing the dialogue of the results of the investigation and reporting at the 'medium' level, (5) closing the story containing the message at the 'good' level, the type of message written; view of life, sincerity, and a call to action. Overall the ability to write knowledge of Malay culture is based on the 'good' range. Based on this the suggestions put forward; feature as a creative essay, very easy to develop by students as novice writers, so that they are interested in composing the potentials of local wisdom; data features on the basis of the results of field research through the process of observation, interviews, investigations and reporting. Based on the suggestions put forward, the literary journalism approach can be developed well in learning creative writing.Keyword: cultural wisdom, literary journalism